2023
DOI: 10.12659/msm.941394
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Visceral Adiposity on Testosterone Levels in American Adult Men: A Cross-Sectional Analysis

Abstract: Background Testosterone decline and deficiency importantly affect men’s health, and may be associated with excessive deposition of visceral adipose tissue. This study was conducted to explore the association between visceral adiposity index (VAI) and testosterone level. Material/Methods A total of 1551 participants from the NHANES 2013–2013 cycle and 2015–2016 cycle were selected for our analyses. The VAI index was calculated based on waist circumference (WC), body mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…In addition, we found that these patients had higher insulin and C-peptide levels, which corresponded to the more severe insulin resistance described above, as confirmed by the difference in HOMA-IR between the two groups (p< 0.001), suggesting to us that hypogonadism may be more related to diabetes control. In addition, there were differences in weight, WC, hip circumference, and BMI between the two groups (all P< 0.001), all of which have been found and repeatedly elucidated in previous studies to be associated with lower TT in males with T2DM ( 26 , 37 39 , 41 ), and there was a significant difference in BMI between the two groups in the present study, which fell in the obese and overweight ranges, respectively, and thus we considered BMI in the subsequent analyses.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, we found that these patients had higher insulin and C-peptide levels, which corresponded to the more severe insulin resistance described above, as confirmed by the difference in HOMA-IR between the two groups (p< 0.001), suggesting to us that hypogonadism may be more related to diabetes control. In addition, there were differences in weight, WC, hip circumference, and BMI between the two groups (all P< 0.001), all of which have been found and repeatedly elucidated in previous studies to be associated with lower TT in males with T2DM ( 26 , 37 39 , 41 ), and there was a significant difference in BMI between the two groups in the present study, which fell in the obese and overweight ranges, respectively, and thus we considered BMI in the subsequent analyses.…”
Section: Discussionsupporting
confidence: 57%
“…However, many covariates are still unknown or difficult to obtain from existing research data. To estimate the independent effect between WWI and sTT, we adjusted for potential confounders by including them as covariates in the model, as suggested by previous studies [ [26] , [27] , [28] ]. Age, gender, race (black, white, and other), educational level (<6th grade, 6–9th grade, and >9th grade), and ratio of family income to poverty (PIR) were derived from the Demographic Variables and Sample Weights questionnaire.…”
Section: Methodsmentioning
confidence: 99%